Protocol for a systematic review and meta-analysis assessing conservative versus liberal intravenous fluid administration in patients with sepsis or septic shock at risk of fluid overload - Anders Perner; Mary Elizabeth Wilcox; Marina Englesakis; Aadil Bharwani; María Lucía Pérez; Tine Sylvest Meyhoff; Praleene Sivapalan (BMJ Open, 2023)
Introduction Intravenous crystalloid fluid resuscitation forms a crucial part of the early intervention bundle for sepsis and septic shock, with the Surviving Sepsis Campaign guidelines recommending a 30 mL/kg fluid bolus within the first hour. Compliance with this suggested target varies in patients with comorbidities such as congestive heart failure, chronic kidney disease and cirrhosis due to concerns regarding iatrogenic fluid overload. However, it remains unclear whether resuscitation with higher fluid volumes puts them at greater risk of adverse outcomes. Thus, this systematic review will synthesise evidence from existing studies to assess the effects of a conservative as compared with a liberal approach to fluid resuscitation in patients at greater perceived risk of fluid overload due to comorbid conditions.Methods and analysis This protocol was registered on PROSPERO and has been drafted following the checklist of Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. We will search MEDLINE, MEDLINE Epub Ahead of Print and In-Process, In-Data-Review & Other Non-Indexed Citations, Embase, Embase Classic, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Web of Science Core Collection, CINAHL Complete and ClinicalTrials.gov. A preliminary search of these databases was performed from their inception to 30 August 2022. The risk of bias and random errors will be assessed using the revised Cochrane risk-of-bias tool for randomised clinical trials and the Newcastle-Ottawa Scale for case–control and cohort studies. If a sufficient number of comparable studies are identified, we will perform a meta-analysis applying random effects model. We will investigate heterogeneity using a combination of visual inspection of the funnel plot as well as the Egger’s test.Ethics and dissemination No ethics approval is required for this study since no original data will be collected. The findings will be disseminated through peer-reviewed publication and conference presentation.PROSPERO registration number CRD42022348181.